Taphonomy and the role of pumas (Puma concolor) in the formation of the archaeological record - Borrero, Luis A.; Martin, Fabiana Maria; Prevosti, Francisco J. (My University, 2018)
Puma transport of prey remains to dens located in overhangs, rockshelters or caves lead to conditions of potential mixing with archaeofaunas. The evidence for puma use of places which before or after were also selected by humans is reviewed, as well as results of taphonomic studies. These studies include not only naturalistic observations, but also excavations of puma dens, and serve to highlight some of the research areas needed in order to understand the role of pumas as active agents in the accumulations of bone assemblages. (c) 2016 Elsevier Ltd and INQUA. All rights reserved.
Keywords: puma; taphonomy; den; archaeology